Vegetation response to obliquity and precession forcing during the Mid-Pleistocene Transition in Western Mediterranean region (ODP site 976) (Quaternary Science Reviews, 2011)
The ODP leg 161 Site 976 (Alboran Sea) is a deep-sea section sampled at a water depth of 1108 m in the Western Mediterranean Sea. Pollen analysis provides a vegetation and climate record of the Mid Pleistocene Transition (MPT), roughly one million years ago. The age-model tied to biostratigraphic events was revised by aligning the pollen climate index (PCI) to Mediterranean (KC01b) and global (LR04) oxygen isotope records. The studied time slice spans the interval w1.09 Ma (MIS 31) to w0.90 Ma (MIS 23). Across this interval, past phytogeography of nowadays extinct taxa, which were rare, allows a successful application of the modern analogues technique (MAT) to quantitative climate reconstructions for the MPT. Five, long-term, obliquity-related vegetation successions (O1 to O5), and eight short-term, precessionrelated vegetation successions (P1 to P8) are observed within the studied interval. These vegetation successions, regardless of their duration, show the same pattern: the progressive replacement of temperate trees by mountainous taxa, and then by herbs and steppe maxima. Precession-related successions correspond, therefore, to as dramatic vegetation changes as those driven by obliquity, including a ﬁnal steppe phase under deteriorated climate conditions. Wavelet analysis of the PCI record shows that the Western Mediterranean experienced a shift at 1.01 Ma from precession-dominated frequencies (1.05e1.01 Ma) to obliquity-dominated frequencies (1.01e0.9 Ma). There is, therefore, an apparent discrepancy between wavelet analysis results and vegetation dynamic analysis (which suggests that obliquity and precession are recorded throughout the entire studied interval). This discrepancy could result from the fact that the PCI record sums, somehow, similar vegetation changes (wet to dry) occurring at different periodicities. Such a complex vegetation dynamics is mathematically rendered through a single parameter (i.e. principal component), which does not successfully catch the subtle combinations of variability occurring at two close periodicities. Furthermore, the pollen-inferred Early Pleistocene vegetation dynamic (and climate) of the Western Mediterranean region does not show a decrease of the obliquity response relative to the precession response at the onset of the MPT

Palynology of the northwestern Mediterranean shelf (Gulf of Lions): First vegetational record for the last climatic cycle - Beaudouin, Célia; Suc, Jean-Pierre; Acherki, Nabila; Courtois, Laurent; Rabineau, Marina; Aloïsi, Jean-Claude; Sierro, Fransisco Javier; Oberlin, Christine (Marine and Petroleum Geology, 2005)
Palynology has been performed for the ﬁrst time on Late Quaternary sediments of the Gulf of Lions. The aim is both to tighten the chronology of seismic proﬁles in the region, and to elucidate the vegetation of southern France during the Last Climatic Cycle. Four cores, taken on the shelf, mostly record Marine Isotope Stages (MIS) 1 and 2 and part of MIS 3 and MIS 5. The latter sediments might have been preserved in a paleodepression on the emergent shelf between the Rhoˆne and the He´rault rivers. It would explain their preservation against transgression and regression erosions of more recent stages. This study also provides a synthesis of palynological continental data collected during the last 40 years in southern Europe. Preliminary comparisons made between the latter and new marine data demonstrate that refugia of Picea and Abies existed in southern France during MIS 3 and MIS 2. The dynamics of Artemisia, deciduous Quercus and Corylus, Abies and ﬁnally Fagus is also reconstructed for the last deglaciation. First results obtained in the Gulf of Lions conﬁrm and complete that synthesis.
Keywords: late quaternary; nw mediterranean sea; palynology

Palynology of the northwestern Mediterranean shelf (Gulf of Lions): First vegetational record for the last climatic cycle (Marine and Petroleum Geology, 2005)
Palynology has been performed for the ﬁrst time on Late Quaternary sediments of the Gulf of Lions. The aim is both to tighten the chronology of seismic proﬁles in the region, and to elucidate the vegetation of southern France during the Last Climatic Cycle. Four cores, taken on the shelf, mostly record Marine Isotope Stages (MIS) 1 and 2 and part of MIS 3 and MIS 5. The latter sediments might have been preserved in a paleodepression on the emergent shelf between the Rhoˆne and the He´rault rivers. It would explain their preservation against transgression and regression erosions of more recent stages. This study also provides a synthesis of palynological continental data collected during the last 40 years in southern Europe. Preliminary comparisons made between the latter and new marine data demonstrate that refugia of Picea and Abies existed in southern France during MIS 3 and MIS 2. The dynamics of Artemisia, deciduous Quercus and Corylus, Abies and ﬁnally Fagus is also reconstructed for the last deglaciation. First results obtained in the Gulf of Lions conﬁrm and complete that synthesis.